Impact of Regional Variation in Bothrops asper Snake Venom on the Design of Antivenoms: Integrating Antivenomics and Neutralization Approaches - Gutiérrez, José María (2010)
Intraspecific snake venom variations have implications in the preparation of venom pools for the generation of antivenoms. The impact of such variation in the cross-reactivity of antivenoms against Bothrops asper venom was assessed by comparing two commercial and four experimental antivenoms. All antivenoms showed similar immunorecognition pattern toward the venoms from adult and neonate specimens. They completely immunodepleted most P−III snake venom metalloproteinases (SVMPs), l-amino acid oxidases, serine proteinases, DC fragments, cysteine-rich secretory proteins (CRISPs), and C-type lectin-like proteins, and partially immunodepleted medium-sized disintegrins, phospholipases A2 (PLA2s), some serine proteinases, and P−I SVMPs. Although all antivenoms abrogated the lethal, hemorrhagic, coagulant, proteinase, and PLA2 venoms activities, monospecific experimental antivenoms were more effective than the polyspecific experimental antivenom. In addition, the commercial antivenoms, produced in horses subjected to repeated immunization cycles, showed higher neutralization than experimental polyspecific antivenom, produced by a single round of immunization. Overall, a conspicuous pattern of cross-neutralization was evident for all effects by all antivenoms, and monospecific antivenoms raised against venom from the Caribbean population were effective against venom from the Pacific population, indicating that geographic variations in venom proteomes of B. asper from Costa Rica do not result in overt variations in immunological cross-reactivity between antivenoms.